Penentuan Tingkat Kompetisi Tajuk Tegakan Jati Hasil Uji Keturunan Umur 11 Tahun di KPH Ngawi - Ronggo Sadono; Meifrida Lasmaria Silalahi (Jurnal Ilmu Kehutanan, 2010)
Determination of  the Competition Level for Growing Space of Teak Canopy from 11-year- old Progeny Test in KPH NgawiThe increasing demand of teak wood should be followed by the increasing of teak forest productivity through intensive silviculture, especially growing space manipulation. The main objective of this research was to determine the growing space competition.The material was measurement data from eleven year progeny test located at the compartment 49a, RPH Sidowayah, BKPH Kedunggalar, KPH Ngawi. The growing space competition was calculated using Hegyi’s competition index. Superior trees were selected to determine competition zone of the subject tree and this result was proposed to calculate the competition index of all trees. Based on the correlation between competition index and tree height, vertical structure was then classified using k-means cluster.Based on 300 superior trees, the competition zone could be determined using reference angle of 66°. The competition index was vary in between 0.00 and 4.23 with average value of 1.18. The correlation between the index and the tree height was found to be low with r = -0.227. Based on this correlation, the vertical structure was classified into four level namely dominant, co-dominant, medium, and suppressed respectively.